A comprehensive review on Sesamum indicum L.: Botanical, ethnopharmacological, phytochemical, and pharmacological aspects. (5th December 2021) - Mili, Ajay; Das, Subham; Nandakumar, Krishnadas; Lobo, Richard
Abstract: Ethnopharmacological relevance: Sesamum indicum L. (Pedaliaceae) is an annual plant, which has been domesticated for well over 5000 years. It is widely cultivated for its seeds and is one of the oldest known oilseed crops. Traditionally, its seeds, seed oil, and different organs of the plant have been used to treat various diseases or conditions like ulcers, asthma, wound healing, amenorrhea, hemorrhoids, inflammations, etc. Aim of the review: The main aim of this review is to provide an outline and to assess the reported ethnopharmacological, phytochemical, pharmacological and toxicological studies of Sesamum indicum L. Materials and methods: An extensive literature survey was done on various search engines like PubMed, Web of Science, Scopus, SciFinder, Google Scholar, Science direct, etc. Other literature sources like Wikipedia, Ethnobotanical books, Chapters were also studied to get maximum information possible on the Sesamum indicum L. Results: Over 160 different phytochemical compounds have been characterized and isolated from seeds, seed oil, and various plant organs, including lignans, polyphenols, phytosterols, phenols, anthraquinones, naphthoquinones, triterpenes, cerebroside, fatty acids, vitamins, proteins, essential amino acids, and sugars using suitable analytical techniques (e.g., LC-MS, GC-MS, HPTLC, HPLC). All the reported pharmacological activities like antioxidant, anticancer, antipyretic, antihypertensive, hepatoprotective, and anti-inflammatory are due to the virtue of these phytochemical compounds. Conclusion: This review mainly highlights the botanical aspect of Sesamum indicum and its phytochemical constituents, ethnomedicinal uses, different pharmacological activities followed by ongoing clinical trials and future prospects. Sesamum indicum has great importance in traditional Indian medicine, which is further supported by modern pharmacological studies, especially in hepatoprotection, inflammation, and cancer. Several researchers have suggested that Sesamum indicum extracts and isolated compounds could have a wide therapeutic potency range. More research is needed to uncover key features of Sesamum indicum in medical practice, such as structure-activity relationships, toxicity, and therapeutic potential. In order to fully explore the plant's potential, safety assessments and implementation of an integrated cultivation method are also areas that need to investigate. Graphical abstract: Image 1